2013
DOI: 10.1007/s13762-013-0192-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of hexavalent chromium from aqueous solutions using autohydrolyzed Scots Pine (Pinus Sylvestris) sawdust as adsorbent

Abstract: In this work, a low-cost lignocellulosic adsorbent with high biosorption capacity is proposed, suitable for the efficient removal of hexavalent chromium from water and wastewater media. The adsorbent was produced by autohydrolyzing Scots Pine (Pinus Sylvestris) sawdust. The effect of the autohydrolysis conditions, i.e., pretreatment time and temperature, on hexavalent chromium biosorption was investigated using energy-dispersive X-ray spectroscopy (EDS) and UV-visible spectrophotometry. The Freundlich, Langmui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…In particular, the increasing costs of conventional adsorbents certainly make lignocellulosic-based materials, composed by natural polymers, one of the most attractive bioadsorbents for wastewater treatment (Sharma and Rajesh, 2014;Kumar et al, 2014). Different studies have demonstrated that lignocellulosic-based polymers have exceptional removal capabilities for certain pollutants such as dyes and metal ions as compared to other low-cost adsorbents and commercial activated carbons (Batzias et al, 2009;Rosas-Castor et al, 2014;Sidiras et al, 2013;Velazquez-Jimenez et al, 2013). Thus, cellulose-based biocomposites, has been widely used in wastewater purification due to its good biocompatibility, and excellent handling, which can be easily formulated into spheres, membranes and hollow fibres.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the increasing costs of conventional adsorbents certainly make lignocellulosic-based materials, composed by natural polymers, one of the most attractive bioadsorbents for wastewater treatment (Sharma and Rajesh, 2014;Kumar et al, 2014). Different studies have demonstrated that lignocellulosic-based polymers have exceptional removal capabilities for certain pollutants such as dyes and metal ions as compared to other low-cost adsorbents and commercial activated carbons (Batzias et al, 2009;Rosas-Castor et al, 2014;Sidiras et al, 2013;Velazquez-Jimenez et al, 2013). Thus, cellulose-based biocomposites, has been widely used in wastewater purification due to its good biocompatibility, and excellent handling, which can be easily formulated into spheres, membranes and hollow fibres.…”
Section: Introductionmentioning
confidence: 99%
“…The moisture content of the material was 8-9% w/w. After screening, the particle sizes isolated were 1-2 mm for sawdust, 1-2 cm for straw and 424 cm for straw scale up [18,19].…”
Section: Methodsmentioning
confidence: 99%
“…Lignin is the third major component of the wood cell wall and it is built up from the phenylpropane nucleus; an aromatic ring with a three carbon side chain, which is promptly available to interact with cationic metal ions (Fatemeh et al 2008). Sidiras et al (2013) have used autohydrolyzing Scots Pine (Pinus Sylvestris) sawdust for removing hexavalent chromium from water and wastewater media. Singh and Prasad (2013b) have also reported that application of natural products such as FYM, SD and RH in Cd-contaminated soil reduced the level of Cd by 36 % under FYM, 23 % under RH and 14 % under SD amended soil.…”
Section: By Using Natural Productsmentioning
confidence: 99%